Injectable therapy in type 2 diabetes mellitus: strategies to improve therapeutic adherence - Olesya Y. Gurova; Valentin V. Fadeev; Ekaterina S. Maloletkina (Сахарный диабет, 2018)
In recent years, the options in treatment of diabetes mellitus type 2 have substantially expanded (currently more than 40 molecules are approved), however, the number of patients with decompensation of diabetes for the period from 2003 to 2014 remains unchanged. In clinical guidelines injecting drugs are given the «final» role as the most effective drugs. However in clinical trials injecting drugs showed a lower adherence compared to oral drugs. Currently injectable glucose lowering drugs include not only insulin but also analogues of glucagon-like peptide-1 (aGLP-1). However, majority of studies of treatment compliance in type 2 diabetes mellitus considered only insulin. Reasons of low compliance are: 1) offering comprehensive programmes for education, monitoring and patient support by primary care physicians; 2) addressing cost and availability issues; 3) prescribing current insulin, also in combination with GLP-1 agonists; 4) use of more simple and convenient devices for injecting insulin.